Correlation between the level of self-esteem and assertiveness in students of the professional academic school of psychology, Universidad de Huánuco, 2018 - Arratea-Castro, Gregorio N. (2019)
Objective: To determine the degree of correlation between the level of self-esteem and assertiveness in students of the Professional Academic School of Psychology of the University of Huánuco from January to March 2018. Methodology and techniques: Observational, prospective, cross-sectional and analytical study. With a correlational design. Results: The average age of the psychology students of the Huánuco University was 21.17 years. It is evident that 56.7% of the students are female and 43.3% of them are male. 50.2% of the students had low average self-esteem levels; 21.4% a medium high self-esteem; 14.9% low self-esteem levels and 13.4% high self-esteem levels. 35.3% of the students had a normal level of assertiveness; 28.9% a light level of assertiveness; 22.4% of the students had difficulties to be assertive and 13.4% had levels of assertiveness. Conclusions: When looking for the relationship between Self-esteem and Assertiveness in students of the Professional Academic School of Psychology of the University of Huánuco, we show that this relationship exists because it was obtained a statistical significance of 0.00 with a correlation degree of 0.75 which shows very good relationship.